2013
DOI: 10.1111/idj.12025
|View full text |Cite
|
Sign up to set email alerts
|

Dental therapists/hygienists working in remote-rural primary care: a structured review of effectiveness, efficiency, sustainability, acceptability and affordability

Abstract: The available data indicates that dental therapist/hygienists have suitable skills and could constitute a valuable asset to meet the dental demands in remote-rural areas. However, the evidence base is limited and of a poor quality. There is a need to put in place 'well-designed interventions with robust evaluation to examine cost-effectiveness and benefits to patients and the health workforce'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The lack of high quality data reported here is consistent with the findings of previous systematic [69][70][71][72] and traditional 8 reviews of acceptability or patient satisfaction with DAs. These reviews also had broad inclusion criteria.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The lack of high quality data reported here is consistent with the findings of previous systematic [69][70][71][72] and traditional 8 reviews of acceptability or patient satisfaction with DAs. These reviews also had broad inclusion criteria.…”
Section: Discussionsupporting
confidence: 90%
“…These reviews also had broad inclusion criteria. Freeman and co-workers 70 could not identify any studies that sought patients' views of the acceptability of care provided by dental therapists in rural or remote settings. From an experiential perspective, the other reviews' conclusions were similar to these; DAs' patients are at least as satisfied as those of dentists across a range of clinical tasks but the quality of the evidence is low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those, in turn, are influenced by the education of the clinician/operator. There need not necessarily be a direct correlation between years of academic training study and effectiveness, however, as has been shown by at least short-term successes with restorations placed by nondentists (Bader et al, 2011;Freeman et al, 2013). It is tempting to assume that treatment decisions depend upon only the patient and the clinician.…”
Section: Session 4 Incorporating New Materials and Techniques Into Cmentioning
confidence: 99%